PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERDASARKAN TEORI APOS UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Siti Halimah; Agung Hartoyo; Yulis Jamiah (Universitas Tanjungpura, 2021)
AbstractThis study aims to develop LKPD based on the APOS theory and improvestudents' ability to understand mathematical concepts. The research methodused is development research with the Borg & Gall model. The developmentsteps carried out are preliminary research and data collection, planning, initialproduct manufacture, initial testing, initial product improvement, limited trials.The research sample was five students of class X MA Al Baariq. Based on theresearch results, LKPD is suitable for use in teaching and learning activitiesand has a validity level of 84%. The results also stated that LKPD is easier touse and easier to understand learning material with a practicality level of81.50%.Keywords: APOS Theory, Conceptual Understanding Skills, LKPD